2006
DOI: 10.1007/s11060-006-9265-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MHC I and NK ligands on human CD133+ glioma cells: possible targets of immunotherapy

Abstract: Mounting evidence suggests that gliomas are comprised of differentiated tumor cells and brain tumor stem cells (BTSCs). BTSCs account for a fraction of total tumor cells, yet are apparently the sole cells capable of tumor initiation and tumor renewal. BTSCs have been identified as the CD133-positive fraction of human glioma, whereas their CD133-negative daughter cells have limited proliferative ability and are not tumorogenic. It is well established that the bulk tumor mass escapes immune surveillance by multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 42 publications
7
81
1
1
Order By: Relevance
“…The inhibition of NK cells is mediated by the inhibitory killer-cell immunoglobulin-like receptors or NKG2A/CD94 that recognize classical or nonclassical HLA class I molecules, respectively, which are often lost or reduced in malignant cells [13,14]. Contrarily to conventional chemotherapy, NK cells appear to recognize and kill undifferentiated stem-like cells [15,16] by virtue of their ability to target non-dividing cells and due to the low expression of MHC class I molecules and possible up-regulation of stress-induced activation ligands [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of NK cells is mediated by the inhibitory killer-cell immunoglobulin-like receptors or NKG2A/CD94 that recognize classical or nonclassical HLA class I molecules, respectively, which are often lost or reduced in malignant cells [13,14]. Contrarily to conventional chemotherapy, NK cells appear to recognize and kill undifferentiated stem-like cells [15,16] by virtue of their ability to target non-dividing cells and due to the low expression of MHC class I molecules and possible up-regulation of stress-induced activation ligands [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Amplified NK cells possess 82.2±10.5% leukomonocytes (mean ± standard deviation) and the therapeutic effects of NK cells are enhanced by simultaneous venous injection with IFN-β. Clinical results demonstrate that autologous NK cells are safe and somewhat effective for the treatment of glioma (19)(20)(21)(22)(23). The present study indicates that allogeneic NK cells exhibit specific cytotoxic activity on glioma cells.…”
Section: Discussionmentioning
confidence: 52%
“…Eisele et al [17], showed that human glioma cells express MICA/B as well as ULBP1-3 and that the expression of these ligands in glioma may be influenced by TGF-β. Moreover, Wu et al [18] Provided evidence that tumor-initiating cells within gliomas−also referred to as glioma stem cells and characterized by their CD133 cell surface marker expression−express NKG2D and NKp30/44/46 ligands. Our results show a perivascular infiltrate of CD20+ cells, and the following statistical differences when associating it with tumor size (p=0.004), histological type (p=0.013), brain infiltration and mode of inflammatory cell infiltration (p=0.000 respectively).…”
Section: Discussionmentioning
confidence: 99%